Molecular Interactions and Cellular Itinerary of the Yeast RAVE (Regulator of the H(+)-ATPase of Vacuolar and Endosomal Membranes) Complex - Smardon, Anne M. (J Biol Chem, 2015)
The RAVE complex (regulator of the H(+)-ATPase of vacuolar and endosomal membranes) is required for biosynthetic assembly and glucose-stimulated reassembly of the yeast vacuolar H(+)-ATPase (V-ATPase). Yeast RAVE contains three subunits: Rav1, Rav2, and Skp1. Rav1 is the largest subunit, and it binds Rav2 and Skp1 of RAVE; the E, G, and C subunits of the V-ATPase peripheral V(1) sector; and Vph1 of the membrane V(o) sector. We identified Rav1 regions required for interaction with its binding partners through deletion analysis, co-immunoprecipitation, two-hybrid assay, and pulldown assays with expressed proteins. We find that Skp1 binding requires sequences near the C terminus of Rav1, V(1) subunits E and C bind to a conserved region in the C-terminal half of Rav1, and the cytosolic domain of Vph1 binds near the junction of the Rav1 N- and C-terminal halves. In contrast, Rav2 binds to the N-terminal domain of Rav1, which can be modeled as a double β-propeller. Only the V(1) C subunit binds to both Rav1 and Rav2. Using GFP-tagged RAVE subunits in vivo, we demonstrate glucose-dependent association of RAVE with the vacuolar membrane, consistent with its role in glucose-dependent V-ATPase assembly. It is known that V(1) subunit C localizes to the V(1)-V(o) interface in assembled V-ATPase complexes and is important in regulated disassembly of V-ATPases. We propose that RAVE cycles between cytosol and vacuolar membrane in a glucose-dependent manner, positioning V(1) and V(0) subcomplexes and orienting the V(1) C subunit to promote assembly.